The effect of water content in soil media on the hatchability of Bractocera dorsalis pupae - Leksono Amin Setyo; Yanuwiadi Bagyo; Rizali Akhmad; Gama Zulfaidah Penata; Agustina Dwi Kameluh; Tesari Tasafima; Zatim Aufa; Imam Muhamad (BIO Web of Conferences)
Fruit flies are polyphagous pests on various important fruit crops. The Bactrocera genus, including Bactrocera dorsalis (Hendel), undergoes a pupation process in the soil. Efforts to control this species in the pupal phase can be done by applying entomopathogenic fungi. Entomopathogenic fungi need a moist environment to grow optimally. This study aims to evaluate the effect of adding water to soil media on the success of B. dorsalis pupae becoming imago. The soil media used comes from orange fields. Soil media is sterilized first before being used to test the success of fruit fly pupation. The addition of water was carried out with the following water and media content ratios: 0 : 1, 0.075 : 1, 0.15 : 1, 0.184 : 1, 0.225 : 1, 0.3 : 1 and 0.5 :1. The pupa is placed in a mica tube with a diameter of 5 cm and poured with granulated soil, so that it reaches a height of 4 cm. Replication was carried out four times. The parameters observed include success in becoming an imago, survival, and normality. The highest percentage of pupae that hatched was found at a water to soil addition ratio of 0.15 to 1 (86.25% ± 5.54). The highest percentage of living imago was also at the same water addition concentration (27.5% ± 1.44), as was the percentage of normal imago (81.25% ± 5.90). However, the death rate at this concentration was also high (58.75& ± 4.73). The highest percentage of abnormal pupae was found in media without the addition of water (0: 1). There was a tendency for success rates to become imago, survival, and normality to decrease at higher water concentrations. The findings of the regression analysis show the survival equation y = -4.33x + 28.75. No pupae successfully hatched at a water concentration of 0.5 to 1 v/v. At concentration after two days, the soil becomes dry and hard to clot. This study recommends using a water concentration of 0.15 to 1 v/v for applications with entomopathogenic fungi to create sufficient soil moisture.